2007
DOI: 10.1051/0004-6361:20077485
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of complex N- and O-bearing molecules in hot molecular cores

Abstract: Aims. We have observed several emission lines of two Nitrogen-bearing (C 2 H 5 CN and C 2 H 3 CN) and two Oxygen-bearing (CH 3 OCH 3 and HCOOCH 3 ) molecules towards a sample of well-known hot molecular cores (HMCs) in order to check whether the chemical differentiation seen in the Orion-HMC and W3(H 2 O) between O-and N-bearing molecules is a general property of HMCs. Methods. With the IRAM-30m telescope we have observed 12 HMCs in 21 bands, centered at frequencies from 86 250 to 258 280 MHz. Results. In six … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
86
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 69 publications
12
86
4
Order By: Relevance
“…Methylene amidogen has previously been found in the cold core TMC-1 (Ohishi et al 1994) and methyl formate and vinyl alcohol have previously been detected in hot cores (Fontani et al 2007;Turner & Apponi 2001). Using criterion (iii) from Section 4 we can rule out methylene amidogen as there are several expected transitions in the frequency range of our observations that are not seen.…”
Section: Moleculementioning
confidence: 73%
“…Methylene amidogen has previously been found in the cold core TMC-1 (Ohishi et al 1994) and methyl formate and vinyl alcohol have previously been detected in hot cores (Fontani et al 2007;Turner & Apponi 2001). Using criterion (iii) from Section 4 we can rule out methylene amidogen as there are several expected transitions in the frequency range of our observations that are not seen.…”
Section: Moleculementioning
confidence: 73%
“…Observations of CH 3 CN transitions show a References. (a) Cesaroni et al (1997), (b) Moscadelli et al (2011), (c) Leurini et al (2007), (d) Sridharan et al (2002), (e) Xu et al (2011), ( f ) Cesaroni et al (1994b), (g) Churchwell et al (1990), (h) Fontani et al (2007).…”
Section: Iras 20126+4104mentioning
confidence: 99%
“…Millimeter lines from complex organic molecules are widely associated with high-mass star forming regions and indeed form one of the signposts of the deeply embedded phase of star formation (e.g., Blake et al 1987;Hatchell et al 1998;Gibb et al 2000;Fontani et al 2007;Requena-Torres et al 2008;Belloche et al 2009;Zernickel et al 2012). Many studies of the chemistry in such regions have been carried out, either through complete spectral surveys of individual sources or by targetting individual molecules in a larger number of sources (see Herbst & van Dishoeck 2009;Caselli & Ceccarelli 2012, for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Remijan et al (2004a) reported the detection of CH 3 CN in the 3mm band using BIMA, and the CH 3 CN was further mapped by Hernández-Hernández et al (2014). Other COMs, such as CH 3 OH, 13 CH 3 OH, CH 3 CCH, CH 3 OCH 3 , C 2 H 5 CN, and C 2 H 3 CN, were reported in several millimeter-band line surveys (Hatchell et al 1998b;Fontani et al 2007). …”
Section: Ngc7538mentioning
confidence: 97%
“…Both cores have a rich inventory of COMs, revealed by extensive line surveys across the millimeter bands (Helmich et al 1994;Helmich & van Dishoeck 1997;Kalenskii et al 1997Kalenskii et al , 2000aWyrowski et al 1999a;van der Tak et al 2000;Ikeda et al 2001;Alakoz et al 2002;Charnley 2004;Sutton et al 2004;Kim et al 2006;Bisschop et al 2007;Fontani et al 2007;Ratajczak et al 2011;Reiter et al 2011;Li et al 2012;Gerner et al 2014;Hernández-Hernández et al 2014;Ligterink et al 2015;Qin et al 2015). (Helmich & van Dishoeck 1997;Fontani et al 2007;Qin et al 2015), and CH 3 OH has two temperature components (Qin et al 2015).…”
Section: W3(h 2 O)mentioning
confidence: 99%